2022
DOI: 10.1155/2022/5515305
|View full text |Cite
|
Sign up to set email alerts
|

Role of NOD-Like Receptors in a Miniature Pig Model of Diabetic Renal Injuries

Abstract: Activation of NOD-like receptor (NLR) signaling pathway can promote downstream cytokine and proinflammatory cytokines release, and inflammation induced by excess nutrients leads to renal metabolic injury. How the NLRs influence metabolic progress and then lead to the renal injury remains poorly investigated. Compared with rodents, minipigs are more similar to humans and are more ideal animal models for human disease research. In this study, we established a diabetic minipig model through a high-sugar and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“… 17 NOD-like receptors (NLRPs and NLRCs) are activated in the diabetic micropig model to promote the expression of downstream inflammatory factors such as IL-6 and IL-18 through TGF-β pathway, causing metabolic inflammation of kidney tissue, and ultimately leading to the occurrence and development of diabetic kidney disease. 18 In this experiment, we found that the serum levels of TGF-β, IL-6 and IL-18 in diabetic kidney disease patients were significantly higher than those in normal diabetic albuminuria group and healthy control group, and were significantly higher in diabetic microalbuminuria. Person analysis found that inflammatory factors IL-6, IL-18 and TGF-β were significantly positive with UACR, and significantly negatively correlated with glomerular filtration rate, indicating that inflammatory response had already occurred in the early stage of diabetic kidney disease and the degree of inflammation was positively correlated with the disease.…”
Section: Discussionmentioning
confidence: 58%
“… 17 NOD-like receptors (NLRPs and NLRCs) are activated in the diabetic micropig model to promote the expression of downstream inflammatory factors such as IL-6 and IL-18 through TGF-β pathway, causing metabolic inflammation of kidney tissue, and ultimately leading to the occurrence and development of diabetic kidney disease. 18 In this experiment, we found that the serum levels of TGF-β, IL-6 and IL-18 in diabetic kidney disease patients were significantly higher than those in normal diabetic albuminuria group and healthy control group, and were significantly higher in diabetic microalbuminuria. Person analysis found that inflammatory factors IL-6, IL-18 and TGF-β were significantly positive with UACR, and significantly negatively correlated with glomerular filtration rate, indicating that inflammatory response had already occurred in the early stage of diabetic kidney disease and the degree of inflammation was positively correlated with the disease.…”
Section: Discussionmentioning
confidence: 58%